1994
DOI: 10.1149/1.2054817
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Thermal Treatments on the Adhesion of Electrolessly Deposited Ni (  P  )  Layers on Alumina Ceramic

Abstract: The adhesion of electrolessly deposited Ni(P) on 96 and 99.5% pure alumina was studied as a function of annealing temperature, up to 580~ The adhesion was measured with the direct pull-off test and the peel test. The interface structure was analyzed with cross-section transmission electron micrographs. Fracture surfaces were analyzed with scanning electron microscopy/energy dispersive x-ray analysis, static-secondary ion mass spectroscopy, and x-ray photoelectron spectroscopy. The optimum annealing temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
5
1
Order By: Relevance
“…The oxidized Ni and P species, the nucleation material and the sulphur compounds, detected with the aid of XPS on fracture surfaces of all of the sample types, indicate the presence of similar compounds as found in the previous studies [4,5]. On the other hand, the TEM cross-section micrograph of the sample with the ZrO2 substrate coating does not show a discrete interfacial layer.…”
Section: Adhesion Mechanismsupporting
confidence: 80%
See 4 more Smart Citations
“…The oxidized Ni and P species, the nucleation material and the sulphur compounds, detected with the aid of XPS on fracture surfaces of all of the sample types, indicate the presence of similar compounds as found in the previous studies [4,5]. On the other hand, the TEM cross-section micrograph of the sample with the ZrO2 substrate coating does not show a discrete interfacial layer.…”
Section: Adhesion Mechanismsupporting
confidence: 80%
“…From these studies evidence has been obtained that, in contrast to what is commonly believed [2], the adhesion is influenced not only by mechanical interactions but also by interface chemical interactions [4,5]. Osaka et al [6] reported similar evidence.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations